2004
DOI: 10.1177/011542650401900160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laparoscopic Roux‐en‐Y Gastric Bypass on Type 2 Diabetes Mellitus

Abstract: Objective: To evaluate pre-and postoperative clinical parameters associated with improvement of diabetes up to 4 years after laparoscopic Roux-en-Y gastric bypass (LRYGBP) in patients with type 2 diabetes mellitus (T2DM). Summary Background Data: The surgical treatment of morbid obesity leads to dramatic improvement in the comorbidity status of most patients with T2DM. However, little is known concerning what preoperative clinical factors are associated with postoperative longterm improvement in diabetes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
197
5
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(228 citation statements)
references
References 27 publications
18
197
5
8
Order By: Relevance
“…A relevant comparison might be with gestational diabetes, in which the escalating insulin demands of pregnancy exceed the capacity of the pancreatic islets to respond, yet normoglycaemia is restored following delivery-a 'remission' that, as we know, is often transient. This is consistent with the observation that hyperglycaemia is most effectively controlled by surgery in those with disease of a shorter duration, whereas those with a longer duration of diabetes or higher treatment requirements derive less benefit [32,39]. In agreement with this, a recent retrospective report highlights the extent to which long-term glycaemic control may eventually deteriorate after gastric bypass [40].…”
Section: Which Is the Better Operation?supporting
confidence: 82%
“…A relevant comparison might be with gestational diabetes, in which the escalating insulin demands of pregnancy exceed the capacity of the pancreatic islets to respond, yet normoglycaemia is restored following delivery-a 'remission' that, as we know, is often transient. This is consistent with the observation that hyperglycaemia is most effectively controlled by surgery in those with disease of a shorter duration, whereas those with a longer duration of diabetes or higher treatment requirements derive less benefit [32,39]. In agreement with this, a recent retrospective report highlights the extent to which long-term glycaemic control may eventually deteriorate after gastric bypass [40].…”
Section: Which Is the Better Operation?supporting
confidence: 82%
“…17 Other studies published since these EBM reports have shown better control of T2DM and hypertension with greater weight loss. 51,52 Evaluation of newer techniques in bariatric surgery The risks and benefits of laparoscopic gastric bypass, that is, the early benefits of the laparoscopic vs the open approach, are omitted in the TEC study. This report fails to mention the shorter length of hospital stay, the significant decrease in pain, and wound complications the early improvement in quality of life and earlier return to work with the laparoscopic approach.…”
Section: Resultsmentioning
confidence: 99%
“…Durch eine Magenbypass-Operation verändert sich zudem die physiologische Antwort auf die an der Blutglukose-und Appetitregulation beteiligten Hormone Ghrelin, Glukagon-like-peptide-1 (GLP-1) und PYY-36 [24,25]. Daher hat sich kürzlich der Begriff der "metabolischen Chirurgie" etabliert [26,27,28].…”
Section: Metabolische Chirurgie -Ein Neuer Therapieansatz Bereits Beiunclassified